Impact of epilepsy on the risk of hospital-treated injuries in Finnish children - Ripatti Liisi; Puustinen Laura; Rautava Päivi; Koivisto Mari; Haataja Leena (Elsevier BV, 2025)
Objectives
To study the effect of epilepsy on the risk of injury in children.
Methods
All first-born singleton children (n = 133055) born in 2001 – 2006 in Finland were included. Data was collected from national registers up to the first hospital-treated injury during the five years following the onset of epilepsy. Four matched controls were chosen for every subject.
Results
Epilepsy had been diagnosed in 0.66 % of children. During follow-up, 12 % of 884 children with epilepsy and 9 % of 3536 controls were hospitalized for injuries (HR 1.387 [95 % CI 1.115 – 1.725]; p = 0.0033). Risk for injuries was higher in boys than girls (p = 0.0057). Mean age at the first injury was 6.8 years (SD 3.3, median 7, range 0–13) in subjects and 7.2 years (SD 3.2, median 8, range 1–13) in controls (p = 0.272). The rate of hospitalization did not differ according to the type of epilepsy. The risks of subjects compared to controls were not significantly different concerning the nature of injury or survival.
Conclusions
Children with epilepsy are at increased risk for hospital-treated injuries. The spectrum of injuries and the risk for death due to injuries are not different in children with and without epilepsy.